2002
DOI: 10.2174/0929866023408760
|View full text |Cite
|
Sign up to set email alerts
|

Promiscuous Binding Nature of Sh3 Domains to their Target Proteins

Abstract: SH3 domains are small but important domains in cell-signaling and function through protein-protein interactions. Their promiscuous nature in binding to polyproline peptides makes them much more important because many SH3 domains from different proteins bind to different proteins having polyproline template on their surface. Very subtle changes in the sequence of SH3 domains and the binding peptides determine the specificity of the peptide binding. Recent observation that SH3 domains bind to non- proline peptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 2 publications
2
31
0
Order By: Relevance
“…Several protein domains have been described in both eukaryotic and prokaryotic systems that are involved in protein-protein interactions in these complexes (Pawson et al, 2002;Ponting, 1997;Sheng & Sala, 2001;Agrawal & Kishan, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Several protein domains have been described in both eukaryotic and prokaryotic systems that are involved in protein-protein interactions in these complexes (Pawson et al, 2002;Ponting, 1997;Sheng & Sala, 2001;Agrawal & Kishan, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…If all family members do function as RasGAP effectors in vivo they may mediate similar, opposing or completely different effects. SH3 domains are relatively promiscuous and subtle differences in the domains and their ligands can alter binding specificity (Agrawal and Kishan, 2002). The contextual differences between the PxxP motifs in the G3BPs could therefore be functionally relevant.…”
Section: G3bps Interact With Rasgapmentioning
confidence: 99%
“…In vitro binding assays with G3BP1 and G3BP2 suggested that the NTF2-like domain of these proteins was responsible for RasGAP binding (Kennedy et al, 2001). It is rare, but not unprecedented, for non-proline motifs to bind SH3 domains (Agrawal and Kishan, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…SH3 domains often bind peptides with modest affinities (5-100 M (5)), and many SH3 domains appear to possess low specificity, binding to various PXXP-containing peptides with similar affinities (6 -10). These observations have led to the establishment of a "promiscuous model," which postulates that the signaling specificity of pathways depends primarily on factors other than the intrinsic binding properties of isolated SH3 domains (11), and that short peptide targets are likely sufficient for SH3 domain function. Arguing against this model, it has been shown that some SH3 domains require an extended target peptide (12-30 residues) to achieve maximal binding affinity (12)(13)(14)(15).…”
mentioning
confidence: 99%